Phylogenetic and morphological study of schismatoglottis (araceae) in Sabah, Malaysia - Nurul Hasanah Harisin (2023)
The tribe Schismatoglottideae is one of the most species-rich and diverse Araceae taxa in Borneo. Schismatoglottideae contains a diverse group of rainforest terrestrial, litophytic or rheophytic herbs centred in Borneo. The genus Schismatoglottis has more than 175 species with the majority endemic in Borneo with strictly geological obligated. This study was carried out to archive these following objectives; (1) To investigate phylogeny construction by using the Internal Transcribed Spacer (ITS) region on selected Schismatoglottis in Sabah, (2) To investigate phylogeny construction by using trnL-F region on selected Schismatoglottis in Sabah, and (3) To mapping the morphology characteristics of the selected Schismatoglottis genus based on constructed phylogenetic tree. A total of 22 taxa were collected from nine different localities within Sabah, these are Kinabalu National Park (Sayap substation), Kadamaian-Kinabalu Park (Kota Belud), Kionsom Recretional Area, Imbak Canyon Conservation Area, Mensalong Forest Reserve (Kota Marudu), Danum Valley Conservation Area, Tawau Hills Park, Sungai Rawog Conservation Area and Mantailang (Tenom) Crocker Range Park. Phylogenetic analyses of Schismatoglottis were carried out in this study based on nuclear of Internal Transcribed Spacer (ITS) and chloroplast DNA (trnL-F) sequences. Analysis of combined datasets analyzed with Maximum Likelihood and Bayesian Inference methods. The phylogenetic relationship of two combined DNA regions was done employing 22 taxa and one outgroup (Apoballis mutata). The phylogenetic tree of combined analysis for ITS gene in this study produced five clades, whereas the phylogenetic tree of combined analysis for trnL-F region in this study produced four clades. Meanwhile, the phylogenetic tree of Maximum Likelihood analysis by using concatenate data, produced two major clades, and the phylogenetic tree of Bayesian Inference analysis using the same concatenate data produced five clades. The outcomes of each of the four different phylogenetic trees yield four sister clades that are identical to one another. The four consistent sister clades give a prove that using two phylogenetic methods (Maximum Likelihood, use heuristic search to find the best tree, while Bayesian Inference use posterior probability) would be needed to confirm the four sister clades. Through genetic, morphological, or other investigations, phylogenetic relationships between various species or organisms are intended to be understood. Due to several variables, including data selection, analysis methods, and underlying assumptions, these studies may yield varying results depending on the methodologies utilised. The data selection and quality, the handling of missing data, the differences in the phylogenetic method utilised, and other factors were the justifications for the divergent results. In conclusion, incorporating morphological and molecular data into phylogenetic research can offer a more comprehensive and robust view on evolutionary relationships, providing a richer and more accurate representation of the tree of life.